Intestinal parasites among food handlers of food service establishments in Ethiopia: a systematic review and meta-analysis - Yonas Yimam; Ambachew Woreta; Mehdi Mohebali (BMC, 2020)
Abstract Background Intestinal parasites remain considerable public health problems in low-income countries where poor food hygiene practice is common. Food handlers, people involved in preparing and serving food, working with poor personal hygiene could pose a potential threat of spreading intestinal parasites to the public in a community. The aim of this systematic review and meta-analysis was, therefore, to synthesize the pooled prevalence estimate of intestinal parasites and associated pooled odds ratio of hygienic predictors among food handlers of food service establishments in Ethiopia that could aid to further bringing down the burden of intestinal parasites and it can also be used as a springboard for future studies. Methods We searched exhaustively for studies Published before 20 April 2019 using eight Databases; PubMed, Science Direct, Web of Science, Scopus, Embase, Google Scholar, ProQuest, and Ovid MEDLINE® complemented by the gray literature search. In the final synthesis, we included twenty study reports. We used the Cochrane Q test and I2 test to assess heterogeneity of studies, while we employed a funnel plot followed by Egger's regression asymmetry test and Begg rank correlation methods to evaluate publication bias. We also performed a point estimates and 95% confidence interval for each study using STATA version 14 statistical software. Results The overall pooled prevalence estimate of intestinal parasites among food handlers of food service establishments in Ethiopia was 33.6% (95%CI: 27.6-39.6%). Among ten intestinal parasites identified from food handlers, Entamoeba histolytica/ dispar (11, 95%CI: 7.9-14.1%) and Ascaris lumbricoides (8.8, 95%CI: 6.4-11.2%) were the most predominant intestinal parasites. Food handlers who washed hands after toilet use had 54% (OR, 0.46, 95% CI: 0.23-0.94) protection from intestinal parasites compared to those who did not. Conclusions This study revealed that intestinal parasitic infections are notable among food handlers of food service establishments in Ethiopia, which may be a risk for transmitting intestinal parasites to food and drinks consumers through the food chain. Thus, periodic stool checkup, training on intestinal parasitic infections and personal hygiene should be applied to reduce public health and socio-economic impacts of parasitic infections.